A comparison of ratio and allometric scaling methods for normalizing power and strength in elite rugby union players - Crewther, B. T.; Gill, N.; Weatherby, R. P.; Lowe, T. (Journal of Sports Sciences, 2009)
In this study, we compared the effectiveness of ratio and allometric scaling for normalizing power and strength in elite male rugby union players. Rugby union forwards (n = 18) and backs (n = 20) were assessed for squat jump and bench throw peak power, and box squat and bench press one-repetition maximum strength. The performance data for the forwards and backs were compared using ratio (P/BM) and allometric scaling (P/BMb), where P represents performance, BM is body mass in kilograms, and b is a power exponent. A proposed allometric exponent (0.67) and exponents (±95% confidence intervals) derived for the box squat (0.33 ± 0.31), bench press (0.45 ± 0.30), bench throw (0.46 ± 0.36), and squat jump (0.64 ± 0.31) exercises were used. In general, the absolute expression of power and strength was superior for the heavier forwards, but after ratio scaling these performance measures then favoured the lighter backs. There were no performance differences between the forwards and backs after allometric scaling using either the proposed or the derived exponents. Thus, allometric scaling may provide a more effective method for normalizing power and strength in elite athletes when body size is a confounding variable.